A simple method for controlling buck-boost SEPIC H-bridge inverter - Pratomo, Leonardus Heru; Paudel, Sushil; Cahyadi, Bagus Kusuma (Institute of Advanced Engineering and Science, 2024)
Over the past decade, much research and development has gone into the use of electric power converters, and the trend is upward. Inverters are employed when converting DC voltage to AC voltage. Typically, inverters perform functions such as voltage boost (to compensate for voltage decrease) or both voltage buck and boost. Other issues to consider include the structure of the inverter topology and the control method. Based on the problem, a study was conducted on a buck-boost inverter that integrates an H-bridge inverter and a single ended primary inductor converter (SEPIC). The H-bridge inverter is widely recognized for its simplicity of operation and always runs in buck mode. The SEPIC converter always runs in buck-boost mode. Since it is unipolar, it can operate as a buck or boost when combined with SEPIC AC-AC. The output voltage is significantly improved because it has several filters to enhance the signal. This hybrid topology is controlled by sinusoidal pulse width modulation, resulting in a straightforward control technique with outstanding performance. The H-bridge inverter operates in index modulation 0-100%, and the SEPIC converter more than 50%. In the lab, a computational and implementation procedure is used to test the effectiveness of the hybrid topology and control method under consideration. The test results show that the hybrid architecture can function within the desired parameters. The proposed inverter has 4.531% THD_V, 4.531% THD_I, and 97.85% efficiency under simulation.